Henry Caldwell Cook, creativity and democratic learning. Issue 2 (15th August 2019) - Howlett, John
Abstract : Purpose: The purpose of this paper is to re-examine the life and work of a forgotten progressive educator – (Henry) Caldwell Cook who was an English and drama teacher at the Perse School in Cambridge, UK. By looking at his key work The Play Way (1917) as well as the small number of his other writings it further seeks to explain the distinctiveness of his thinking in comparison to his contemporaries with a particular focus upon educational democracy. Design/methodology/approach: The work was constructed primarily through a reading of Cook's published output but also archival study, specifically by examining the archives held within the Perse School itself. These consisted of rare copies of Cook's written works – unused by previous scholars – and materials relating to Cook's work in the school such as his theatre designs and a full collection of contemporary newspaper reviews. Findings: The paper contends that Cook's understanding of democracy and democratic education was different to that of other early twentieth century progressives such as Edmond Holmes and Harriet Finlay-Johnson. By so doing it links him to the ideas of progressivism emergent in America from John Dewey et al. who were more concerned with democratic ways of thinking. It therefore not only serves to resurrect Cook as a figure of importance but also offers new insights into early twentieth century progressivism. Originality/value: The value of the paper is that it expands what little previous writing there has been on Cook as well as using unused materials. It also seeks to use a biographical approach to start to better delineate progressive educators of the past thereby moving away from seeing them as a homogenous grouping.